6-2a=3a-9

Simple and best practice solution for 6-2a=3a-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2a=3a-9 equation:


Simplifying
6 + -2a = 3a + -9

Reorder the terms:
6 + -2a = -9 + 3a

Solving
6 + -2a = -9 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
6 + -2a + -3a = -9 + 3a + -3a

Combine like terms: -2a + -3a = -5a
6 + -5a = -9 + 3a + -3a

Combine like terms: 3a + -3a = 0
6 + -5a = -9 + 0
6 + -5a = -9

Add '-6' to each side of the equation.
6 + -6 + -5a = -9 + -6

Combine like terms: 6 + -6 = 0
0 + -5a = -9 + -6
-5a = -9 + -6

Combine like terms: -9 + -6 = -15
-5a = -15

Divide each side by '-5'.
a = 3

Simplifying
a = 3

See similar equations:

| 8x+4y=70 | | 2(1c-3)+12=5c-2c | | B=q+qwf | | 3x-5=2x-1 | | 4x^2+10x+16=0 | | 2(e-3)=5 | | 8b+3=10b-2(b-2)+3 | | 1(6x+7)=3*5 | | 6x+15-2x=0 | | 3a+2=32 | | 12x-4y+10=0 | | 14=8z-30 | | 11x+24=3x+60 | | (2x-3)-2(3x+2)=y | | 6n-3=-3+6n | | 4(2w+4)=3(5w-4) | | 44-3n=4+n | | 12+x=2-4x | | 6x+15=8x | | 33=3x-7-11x | | -1+5x=-46 | | 18-4x=6(x+4) | | 2.2h+0.4=2.2h-0.2 | | 5(3c+2)=40 | | 7y-11-2y=3y-22 | | 12x+5y-1=0 | | 5x^4+3x^2+1=0 | | 12-2n=27 | | 1=2x+3 | | 4+9y-3=9y+6 | | 5-5x=25 | | 12-3f+15=-13+7f |

Equations solver categories